Me(Pe)rantau “si Malin Kundang” in the novels of Minangkabau authors after PRRI - Ronidin, Ronidin; Sudibyo, Sudibyo; Indrastuti, Novi Siti Kussuji (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This article is about the phenomenon of me(pe)rantau tragic among Minangkabau people in four novels by Minangkabau authors after Pemerintahan Revolusioner Republik Indonesia (PRRI), namely Panggilan Tanah Kelahiran by Dt. B. Nurdin Jacub, Saraswati Si Gadis dalam Sunyi by A.A. Navis, Warisan by Chairul Harun, and Bako by Darman Moenir. These famous novels after PRRI are sociological and philosophical based novels that express the author's worldview at the maximum level of coherence. In the analysis of these four novels, Lotman's narrative text theory is applied to elaborate the structure of literary works as a conceptual construction centered on the idea of binary opposition. Lotman's elaboration reinforces Eco's view that certain cultural units become meaningful when placed within another cultural unit that is opposed to them. Based on the analysis, the novels that are the subject of this study place the overseas world (dunia rantau) as a source of problems for the Minangkabau people. The characters who encounter the overseas world (dunia rantau) are positioned as